The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--1189
|View full text |Cite
|
Sign up to set email alerts
|

Peer Review In Engineering Courses As A Learning Tool

Abstract: Engineering students will often submit assignments that have not been checked for accuracy or whether the results make sense, and rarely are there high marks for presentation. While this is completely unacceptable and unethical in professional engineering, this disturbing trend has become more common (and even acceptable) in the classroom. Many students are defining success as the act of submission of an assignment, while showing little concern for its content or presentation. A learning tool is proposed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The benefits of peer-review systems in an academic learning environment are generally acknowledged (e.g. [15]- [17]). Just before our own online peer-review platform was launched, a similar system was launched in Sweden [18] as part of a wholly student initiative to test the potential of such a service for thesis-writing support.…”
Section: Activities To Keep a Writing Support Learning Community Engagedmentioning
confidence: 99%
“…The benefits of peer-review systems in an academic learning environment are generally acknowledged (e.g. [15]- [17]). Just before our own online peer-review platform was launched, a similar system was launched in Sweden [18] as part of a wholly student initiative to test the potential of such a service for thesis-writing support.…”
Section: Activities To Keep a Writing Support Learning Community Engagedmentioning
confidence: 99%
“…While peer review seems to be an appealing way to off-load grading time and effort onto students, faculty may worry that the feedback students receive from their peers will not be effective [43]; indeed, without training or structure, students may give superficial feedback ("Great job") or even poor feedback [43,48]. While there are many variants of peer review, here we focus on the role peer review can have in supporting the peer reviewer's own learning [49]meaning the value of peer review is for the person doing the reviewing [50][51][52]. Peer review has been shown to enhance retention of concepts for undergraduates in engineering coursework [53], to support improvement in understanding [23,54] and in writing quality [55,56].…”
Section: Learning To Write In a Disciplinementioning
confidence: 99%
“…Peer review is an important aspect in the work of practicing engineers and knowing this can motivate the students to take the peer assessment more seriously. (10) Page 14.1140.5…”
Section: Peer Assessmentmentioning
confidence: 99%